Accumulation measurements from stake farm Neumayer Pegelfeld Spuso, Ekström Ice Shelf, Antarctica, 2013 - Reppert, Valerie; Regnery, Julia; Eisen, Olaf; Weller, Rolf; Jurányi, Zsófia (In: Reppert, Valerie; Eisen, Olaf; Weller, Rolf; Jurányi, Zsófia (2025): Time series of accumulation measurements from stake farm Neumayer Pegelfeld Spuso, Ekström Ice Shelf, Antarctica, since 2009 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.987214, 2025)
This publication series contains the accumulation measurements from stake farm Pegelfeld Spuso on the Ekström Ice Shelf, Antarctica. The stake farm at the Air Chemistry Observatory (Spuso), located approximately 1.5 km to the south of the present Neumayer Station, has been in operation since September 2009. It consists of 16 aluminum poles (balise), placed in a grid of 4 x 4 with a spacing of 10 m. Readings have been carried out in approx. weekly intervals by the overwintering staff of the air chemistry observatory. Each data set in the series contains all measurements of each stake from one calendar year in a tsv file, the average accumulation of the stake farm for each measurement and the standard deviation of the stake farm for each measurement. The data sets are accompanied by figures illustrating the development of the cumulative accumulation since the beginning of the measurements to date, a bar chart of the monthly accumulation for the year and a collection of panels (one panel per measurement) illustrating the variation of accumulation within the stake farm.
Keywords: Antarctica; Neumayer Station; snow accumulation